The Use of TikTok Application to Improve Students’ Speaking Skills at Senior High School - Salsabilah Reynanda; Hastini Hastini; Grace Novenasari Manurung; Zarkiani Hasyim (Universitas Pahlawan Tuanku Tambusai, 2026)
TikTok has become one of the most widely used social media platforms among students and offers various interactive features, such as short-video creation, audio recording, and content sharing, which have the potential to support language learning and speaking practice. This study aimed to determine whether the use of the TikTok application could improve students’ speaking skills and to identify the most improved aspect of speaking. This research employed a quantitative method with a quasi-experimental design conducted at SMA Negeri 1 Moutong. The sample consisted of 26 students in the experimental group and 24 students in the control group. Data were collected through speaking tests administered in pre-test and post-test sessions. The mean score of the experimental group increased from 46.42 in the pre-test to 86.42 in the post-test, while the control group increased from 35.54 to 48.63. The data were analyzed using the Wilcoxon Signed Rank Test. The results showed that the significance value of the experimental group was 0.000 and that of the control group was 0.001, indicating a significant improvement in students’ speaking skills after the implementation of TikTok. Among the three aspects of speaking, accuracy showed the greatest improvement. Therefore, the TikTok application was found to be effective in improving students’ speaking skills.